EFFECT OF MULTI PASS HIGH ENERGY MILLING ON MORPHOLOGY AND RHEOLOGICAL PROPERTIES OF CARBON NANOTUBES - Darsono, Nono (Pusat Penelitian Metalurgi dan Material - LIPI, 2014)
EFFECT OF MULTI PASS HIGH ENERGY MILLING ON MORPHOLOGY AND RHEOLOGICALPROPERTIES OF CARBON NANOTUBES. Multi pass high energy milling was utilized in order to cut anddisperse carbon nanotubes (CNTs) suspension. The purpose is to maintain the crystallinity and suppress thedamage. One until five passes gave increase in D- to G-band ratio which means increasing the damage, at thevalue range from 0.1 to 0.2. The ratio is still lower compare 2-hour high energy milling and 120-hourconventional ball milling, at the value of 0.5 – 0.3. The rheological properties was not altered dramatically. It isindicated that the milling only tears down the aggeregates into small fraction of entangled CNTs treads.